2020
DOI: 10.1186/s12978-020-0888-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing sexual and reproductive health of Muslim women: a systematic review

Abstract: Background: In Islamic societies, issues related to sexual and reproductive health (SRH) are rarely discussed and considered sensitive subjects. This review aimed to identify any personal, religious, cultural, or structural barriers to SRH service and education among Muslim women worldwide. Methods: A search for qualitative and quantitative studies was conducted on seven electronic databases. A narrative synthesis using thematic analysis was conducted. Results: Fifty-nine studies were included from 22 countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
105
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(118 citation statements)
references
References 90 publications
(269 reference statements)
8
105
0
5
Order By: Relevance
“…Cultural beliefs, poor SRH knowledge, and negative attitudes towards SRH and contraception are also common among Muslim women. (33) In corroboration with other studies conducted in Uganda (2,7,10), our study shows an inversely signi cant association between STI status and coming from the northern region of Uganda. The northern region is classi ed among the rural regions of Uganda, so our results are consistent with ndings from other studies conducted in Uganda (34,35), which revealed that living in rural regions, including northern Uganda, was protective against STI acquisition.…”
Section: Discussionsupporting
confidence: 91%
“…Cultural beliefs, poor SRH knowledge, and negative attitudes towards SRH and contraception are also common among Muslim women. (33) In corroboration with other studies conducted in Uganda (2,7,10), our study shows an inversely signi cant association between STI status and coming from the northern region of Uganda. The northern region is classi ed among the rural regions of Uganda, so our results are consistent with ndings from other studies conducted in Uganda (34,35), which revealed that living in rural regions, including northern Uganda, was protective against STI acquisition.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies in Africa (Abdi et al, 2020) and worldwide noted many potential causes of decreased contraception use in some Muslim communities. This includes misinterpretations of Islamic teachings on whether contraception is allowed, cultural preference for boys and large family sizes, beliefs that contraceptive use indicated infidelity or could lead to infertility, and the belief that sexual education may promote promiscuity (Alomair et al, 2020). Islamic and Traditionalist women in Ghana are more likely than other religious groups to use contraceptives covertly than non-covertly, and to voice concern over dire consequences if their contraception use is not kept confidential (Baiden et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Like other LMICs, we also found considerable seasonal migration of respondents, and faced di culty in identifying listed respondents in a cluster. A study conducted in Bolivia, Kenya, and South Africa showed similar nding of attrition rates between survey rounds and interviewer team tracked, followed and reinterviewed 84% of those women moved [27]. In our study, coordinating two teams to work in tandem and begin interviews immediately once each cluster's household listing was completed helped to minimize attrition between data collection activities.…”
Section: Discussionmentioning
confidence: 52%